Resolving the Crisis of Secular Monetary System Through Islamic Intellectual Revival - Azah Atikah Anwar Batcha; Mohd Hilmi Ramli (Penerbit Hellow Pustaka, 2025)
This paper explores the insights to the solution against secular monetary system by drawing on the philosophical thoughts of Syed Muhammad Naquib Al-Attas. This paper argues that the Muslim world's economic and civilizational decline is deeply rooted in a crisis of knowledge, marked by the loss of adab (right action and proper place), the erosion of authentic leadership, and the secularization of thought. Al-Attas identifies this as a vicious cycle caused by the confusion of knowledge and the disconnection of metaphysical truths from worldly systems. He critiques secularization as a philosophical and scientific program that strips away the spiritual dimension from nature, politics, and morality, leading to a worldview where monetary systems like fiat money are legitimized without intrinsic value, relying instead on state authority and public trust. While fiat money serves as a central medium of exchange in modern economies, created through mechanisms such as central banking and fractional reserve lending, its detachment from any real commodity base raises profound concerns about inflation, instability, and systemic inequality. This paper contends that the real challenge for Muslims is not merely economic or political, but fundamentally intellectual and spiritual. Positive resistance must therefore begin with a reorientation of knowledge rooted in the Islamic worldview, reviving metaphysical consciousness and ethical clarity. Revisiting the concept of money is essential, especially when a secular system is globally enforced regardless of religious beliefs, posing a threat to moral order and the long-term sustainability of society.